Morpho-agronomic characterization of Indian soybean for grouping and varietal protection - Ramteke, Rajkumar; Murlidharan, Pooja; Shivakumar, M.; Gireesh, G.; Ramesh, S.V. (The Indian Journal of Genetics and Plant Breeding, 2016)
Eighty-six soybean varieties differing for various morphological characters were characterized for DUS traits during the kharif seasons from 2007 to 2010 to protect these varieties under Protection of Plant Varieties and Farmers Rights Act (PPV&FRA) 2001. Results of their PCA revealed that days to 50 % flowering, plant height and nodes per plant traits accounted for the most variability. The cluster analysis grouped 86 varieties in to 13 groups. The present study proposes sets of hybridization between the high and low mean yield clusters to achieve yield gain in soybean.